The impact of incentives on employee performance in government organizations (The International Journal for Scientific Research, 2026)
This study aimed to measure the extent of the impact of both material and moral incentives on the performance of employees in some government departments. The study was conducted on a random sample of 83 employees from several government departments, and a questionnaire was used as the data collection tool. The results showed that all respondents confirmed that material and moral incentives have a significant impact on employee performance as well as on their strong organizational loyalty. The findings also revealed that the majority of employees were not satisfied with the incentives provided to them. In addition, a large proportion of the sample emphasized the role of promotion in enhancing loyalty and job satisfaction.The study concluded with a set of recommendations, the most important of which are the need to develop the incentive system in a way that aligns with employees’ needs, to place greater emphasis on the promotion system and material incentives due to their importance from employees’ perspective, and to continue providing moral incentives.
Keywords: Material Incentives; Moral Incentives; Employee Performance; Government Organizations